Brokering activities and learning mechanisms at the boundary of educational research and school practice. (August 2018) - Hartmann, Ulrike; Decristan, Jasmin
Abstract: The interview study explores in what kind of settings people broker at the boundary of educational research and school practice and what kind of learning they experience. Learning mechanisms (identification, coordination, reflection, transformation) were related to three settings (research projects in schools, network activities, professional development). Responses by 18 individuals indicate that all three settings allowed for learning via identification, reflection, and coordination. Still, respondents that solely broker in the setting of professional development were less likely to learn via all three mechanisms. Transformation was only realized in settings that enabled people to establish forms of joint project work. Highlights: Teachers and researchers reported on brokering activities. Brokering occurred in research projects, networks, and professional development. All settings enable learning mechanisms (identification, reflection, coordination). Solely brokering in PD implied the lowest chance to learn via all three mechanisms. Mechanism of transformation mainly emerged in co-constructive research projects.